(3GdLGeY dCMcGe GdbQBf hGdeHjf deG JVefg ef GdSfI hBj GdaQbGf (B/s - (3GdbQWHj, eMeO Hf CMeO Hf CHj HcQs (3Jhaj (B671 (3gLQjs; (3GdJQcj, YHO Gddg Hf YHO GdeMSfs 1359 (3gLQj(B-s; (3YQbShSj, eMeO QVhGfs; (3GdNf, eMeO CfS eUWais; (3MHhT, eGgQs; (3CMeO, ZjGK GdMGLs; (3cQje GdOjf, eMeO eYJRs; (3eGeh, QVhGfs; (3GdeZQHj, aGOjs ((3HjQhJ (B- (3dHfGf (B:s (3eDSSI GdQSGdI ,s, 2013)
(3JaSjQ GdbQWHj gh cJGH LeY JaSjQ GdbQBf cGedG hGSeg zGdLGeY dCMcGe GdbQBf, hGdeHjf deG JVef ef GdSfI hCMcGe GdaQbGfy(B. (3deDdag GdEeGe CHh YHO Gddg eMeO Hf CMeO GdCfUGQj GdbQWHj GdeJhai SfI (B671 (3g`(B. (3hgh JaSjQ LGeY dBjGJ GdbQBf LejYG hdcfg jQcR HUhQI TGedI Ydi BjGJ GdCMcGe aj GdbQBf GdcQje(B. (3GdcJGH ef CaVd cJH GdJaSjQ GdJj YfjJ HGdCMcGe(B. (3hgh aQjO aj HGHg(B. (3ceG Cfg ef CLeY eG Ufa aj gPG Gdaf(B. (3hUa HCfg ef CLd GdJaGSjQ hCYXegG faYG, CSbW efg eDdag GdJhGQjN hGdbUU, hCKHJ YhVgG CMcGe GdbQBf hGSJfHGW GdCOdI, hPcQ GdbQGAGJ hGdfGSN hGdefShN(B.s
(3GdeLdO GdQGHY hGdYTQhf jJVef GdagGQS GdYGeI (B/ (3TGQc aj EYOGO gPG GdLRA eMeO CfS GdNf, eGgQ MHhT, ZjGK GdMGL CMeO, eMeO eYJR cQje GdOjf, QVhGf eGeh, aGOj GdeZQHj(B.s
Keywords: (3GdbQBfs -- (3JaGSjQ abgjIs -- (3CMcGe GdbQBfs